Statistical methods in research - Johnson, Palmer O. (Prentice-Hall, 1949)
Contents: Chapter 1: The realm of statistics; Chapter 2: Probability and Likelihood; Chapter 3: Sampling Distributions; Chapter 4: The testing of statistical hypotheses; Chapter 5: Current Procedures in testing statistical hypotheseses, ...